Vicarship of Stanislaus Pereira - Mumbai Archive Project Team (Jio Institute, 2024)
During the vicarship of Stanislaus Pereira (1953-1974), Our Lady of the Rosary church underwent a comprehensive interior and exterior refurbishment to give it a more contemporary look.